ORGAN DONATION AND PERSONALITY AND PSYCHOSOCIAL VARIABLES RELATED - Rando Calvo, Belén; Blanca Mena, María José; Frutos Sanz, Miguel A. (Anales de Psicología / Annals of Psychology)
The purpose of the present research is to determine the links between personality and psichosocial variables and attitudes toward organ donation and transplantation. The subjects have answered several psychological questionnaires and a survey of attitudes toward organ donation. The results show that there is no association between these factors and the last one, except those variables about the relationship within a group. However, beliefs, attitudes and previous experience regarding organ donation promote favorable attitudes to the organ donation and transplantation.